1991
DOI: 10.1128/jb.173.17.5403-5405.1991
|View full text |Cite
|
Sign up to set email alerts
|

Effects of homocitrate, homocitrate lactone, and fluorohomocitrate on nitrogenase in NifV- mutants of Azotobacter vinelandii

Abstract: Azotobacter vinelandii DJ71, which contains a mutation in the nifV gene, was derepressed for nitrogenase in the presence of homocitrate. When dinitrogenase was isolated from this culture, it was found to be identical to the wild-type dinitrogenase. However, when the same NifV-strain was derepressed in the presence of erythrofluorohomocitrate, a homocitrate analog which produces a nitrogenase with wild-type properties in vitro, the isolated dinitrogenase was characteristic of the NifV-enzyme. These data show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…In previous studies (18,22) NifV Ϫ mutants of Klebsiella pneumoniae and A. vinelandii were found to reduce acetylene levels even though they are unable to fix nitrogen. Thus, strains CA115 and CA116 were tested for acetylene reduction capability and strains CA and CA11.71 were used as positive and negative controls, respectively.…”
Section: N/mentioning
confidence: 99%
“…In previous studies (18,22) NifV Ϫ mutants of Klebsiella pneumoniae and A. vinelandii were found to reduce acetylene levels even though they are unable to fix nitrogen. Thus, strains CA115 and CA116 were tested for acetylene reduction capability and strains CA and CA11.71 were used as positive and negative controls, respectively.…”
Section: N/mentioning
confidence: 99%
“…Since NifV Ϫ mutants of K. pneumoniae (27) and A. vinelandii (24) are able to reduce acetylene even though they are unable to grow diazotrophically, it was of interest to test the AnfG and VnfG mutant strains for their abilities to reduce acetylene. The results of a typical experiment are given in Table 2.…”
Section: Vol 177 1995mentioning
confidence: 99%
“…First, it was shown that a small organic molecule, later shown to be homocitrate (4), is required for the in vitro biosynthesis of FeMo cofactor (3). Second, the addition of homocitrate to cultures of Klebsiella pneumoniae or Azotobacter vinelandii nifV mutants cured both their diazotrophic growth and their biochemical phenotypes (5,12). Third, [ 3 H]homocitrate could be incorporated into FeMo cofactor during its in vitro formation and an organic constituent extracted from purified MoFe protein was identified by nuclear magnetic resonance spectroscopic analysis as homocitrate (6).…”
mentioning
confidence: 99%
“…It might also be possible to use substituted forms or analogs of the homocitrate precursors to form homocitrate analogs. The availability of homocitrate analogs, as well as of radioactively labeled homocitrate, would be useful in expanding the approach described by Madden et al (11,12) to monitor the fate of homocitrate during FeMo cofactor formation and to determine the role of homocitrate in nitrogenase catalysis. (iii) Although it is clear that NifV catalyzes homocitrate formation, it is not yet known how Mo becomes coordinated to homocitrate, nor is it known how homocitrate and Mo become incorporated into FeMo cofactor.…”
mentioning
confidence: 99%